Extracting knowledge from the web and social media for progress monitoring in public outreach and science communication - Scharl, Arno; Herring, David D. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Given the intense attention that environmental topics such as climate change attract in news and social media coverage, key questions for large science agencies such as the National Oceanic and Atmospheric Administration (NOAA) are how different stakeholders perceive the observable threats and policy options, how public media react to new scientific insights, and how journalists present climate science knowledge to the public. This paper investigates the potential of semantic technologies to address these questions. It introduces the NOAA Media Watch and presents a detailed case study of how the metrics and visualizations of the webLyzard Web intelligence platform are used to track information flows across online media channels. Building upon this platform, we present a novel framework to measure the impact of science communication and public outreach campaigns – through a combination of quantitative and visual methods that go beyond sentiment analysis and related opinion mining approaches.